'Haemophilus quentini' in the urethra of men complaining of urethritis symptoms. Issue 1 (January 2018) - Horie, Kengo; Ito, Shin; Hatazaki, Kyoko; Yasuda, Mitsuru; Nakano, Masahiro; Kawakami, Kyojiro; Fujita, Yasunori; Ito, Masafumi; Ezaki, Takayuki; Deguchi, Takashi
Abstract: We isolated a cryptic genospecies of Haemophilus influenzae referred to as ' Haemophilus quentini ' in the urethra of 3 men complaining of urethritis symptoms. H. influenzae strains, which had been isolated from the urethra in 77 of 1518 men complaining of urethritis symptoms, identified by the conventional test, and stored, were re-cultured for this study. Sixty-seven strains surviving storage were screened by a PCR-based assay specific for the cryptic genital Haemophilus genospecies. Three strains (HI09003, HI11006, and HI14016) were screened by PCR and identified as ' H. quentini ' by 16S rRNA sequencing. The men positive for HI09003 and HI11006 were diagnosed as having non-chlamydial non-gonococcal urethritis (NGU), and their demographic and clinical features were similar to those of NGU caused by other pathogens. The man positive for HI14016 was ultimately diagnosed as having condyloma acuminatum on the glans. The 3 strains of ' H. quentini ' produced no β-lactamase and were susceptible to ampicillin and other antimicrobial agents, including cephalosporins, fluoroquinolones, tetracyclines, and macrolides, recommended for treatment for urethritis. ' H. quentini ' would be an uncommon pathogen in men with urogenital infections. Based on the clinical features of the two patients with ' H. quentini '-positive NGU, it would be difficult to predict the presence of ' H. quentini ' in the urethra. The 3 strains of ' H. quentini ' were susceptible to a variety of antimicrobial agents. Further accumulation of data regarding ' H. quentini ' infections is needed to characterize the pathogenic roles of this genospecies in urogenital infections and to establish appropriate management of ' H. quentini ' infections.